Isothermal and non-isothermal drying behavior for grape (Vitis vinifera) by new improved system: exergy analysis, RSM, and modeling - Aydogmus, Ercan; Demirpolat, Ahmet B.; Arslanoglu, Hasan (Springer Heidelberg, 2022)
In this study, drying of grape (Vitis vinifera) in isothermal and non-isothermal conditions has been done with the newly improved proportional integral derivative (PID) system. The average energy efficiency has been calculated in the processes in which the grapes are dried is 53.4% in the isothermal PID system, 59.7% in the non-isothermal PID system, and 30.5% in the tray dryer (forced convection). To maximum exergy efficiency in the tray dryer, the experimental optimization is made according to the response surface methodology (RSM). In the RSM design, the results have been evaluated by working at different airflow rates (1.5 m/s, 2.2 m/s, 2.9 m/s) and different temperatures (298 K, 308 K, and 318 K). In natural conditions, the drying of grapes took approximately 8 days in the sun and 11 days in the shade. A new shrinkage model has been improved based on the transformation rate, considering the drying behavior of grape grains. The consistency of the obtained model equation with the experimental data has been determined with the help of statistical analysis (R-2 0.9987, SST 0.0098). Moreover, when the diffusion behavior of grapes has been investigated, it is determined that both temperature and airflow rate increase the effective diffusion coefficient in the tray dryer. The maximum effective diffusion coefficient in the tray dryer is 2.11.10(9) m(2)/s at a temperature of 318 K and an airflow rate of 2.9 m/s.
Keywords: Grape drying; Exergy efficiency; Shrinkage model; Effective diffusion; RSM